2021
DOI: 10.1016/j.ebiom.2021.103522
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning-based radiomic nomogram for prognosis and treatment decision in advanced nasopharyngeal carcinoma: A multicentre study

Abstract: Background: Induction chemotherapy (ICT) plus concurrent chemoradiotherapy (CCRT) and CCRT alone were the optional treatment regimens in locoregionally advanced nasopharyngeal carcinoma (NPC) patients. Currently, the choice of them remains equivocal in clinical practice. We aimed to develop a deep learning-based model for treatment decision in NPC. Methods: A total of 1872 patients with stage T3N1M0 NPC were enrolled from four Chinese centres and received either ICT+CCRT or CCRT. A nomogram was constructed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 33 publications
0
37
0
1
Order By: Relevance
“…Various imaging-based radiomics models have been proposed to predict treatment responses in different cancers (Liu et al, 2021;Rallis et al, 2021;. Zhong et al, 2021) with the hypothesis that these selected imaging features reflect specific tumor phenotypes (Lambin et al, 2012;Aerts et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Various imaging-based radiomics models have been proposed to predict treatment responses in different cancers (Liu et al, 2021;Rallis et al, 2021;. Zhong et al, 2021) with the hypothesis that these selected imaging features reflect specific tumor phenotypes (Lambin et al, 2012;Aerts et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A few earlier studies tried to measure FDG uptake heterogeneity by using different quantitative measures, including SUVmax/SUVmean [67], SUV standard deviation/SUVmean [68] and the derivative of the volume-threshold function [69]; however, a more recent study [13] using the radiomics approach found skewness (a first-order feature) to be a predictor of relapse-free survival and uniformity (a texture feature) to be a predictor of overall survival, which improved the prognostic stratification of other risk factors found by using multivariate analysis, namely age and serum EBV DNA load. A large multicenter study recently showed that treatment decision and prognosis for specific stages could reliably based on a radiomic based nomogram [70]. However, this study again used MRI for imaging.…”
Section: Nasopharyngeal Carcinomamentioning
confidence: 98%
“…76 Classifiers have been used on radiomics features in serial patient scans to correlate with underlying pathology or as descriptors of treatment response. 77,78 With widespread application of AI to clinical problems, some foundational issues of machine learning algorithms have come to the fore. 79 Specifically, data heterogeneity, unintended bias, and inadequate validation metrics were identified as root causes in two recent prediction failures and false-negative results of AI applications.…”
Section: Clinical Research and Heterogeneity-based Treatmentmentioning
confidence: 99%